Marketing Strategy of Vehicle Finance - Agarwal, Nikhil Ranjan; Gupta, K. C (Journal of Commerce and Trade, 2011)
This paper briefly tries to evaluate the marketing strategy of vehicle finance. For this purpose, an empirical study is undertaken on Western Uttar Pradesh vehicle finance companies covering Bareilly, Moradabad, Meerut and Ghaziabad. The researcher measures and evaluates current state of customers’ satisfaction or dissatisfaction with regard to purchase made by consumers belonging to middle income group. This research examines the impact of vehicle finance activities on consumers, marketing intermediaries and other related group. The result of this empirical study reveals that there is no association between consumers’ overall experience as a customer of vehicle finance schemes and measure of consumers’ awareness about terms of vehicle finance and sources of information on various vehicle finance schemes.